Buya Yahya's da'wah message and crisis communication strategy in responding to the Covid-19 pandemic - Asna Istya Marwantika; Dawam Multazamy Rohmatullah (Jurnal Ilmu Dakwah, 2022)
Purpose - The purpose of this study was to examine the da’wa message and crisis communication strategy carried out by Buya Yahya in responding to the COVID-19 pandemic on YouTube Al-Bahjah TV in the 2020-2022 period.Method - This research uses a qualitative approach with a descriptive type of research. Data collection techniques through observation and documentation. Data analysis techniques use qualitative content analysis in the form of data collection, data coding, data analysis and data interpretation.Result  -  The results showed that Buya Yahya's contribution in responding to the COVID-19 pandemic in Indonesia through Al-Bahjah TV's YouTube for the period of March 2020 to April 2022 by amplifying da'wah messages as many as 76 videos.  The result of the categorization of Buya Yahya's proselytizing message in the form of sharia themes dominates with a percentage of 65%.  Moral themes with a percentage of 26%, and akidah themes of 9%. Crisis communication carried out by Buya Yahya using a message strategy in the form of instructing information and adjusting information.Implication –This research explores daí's contribution in responding to the COVID-19 pandemic. Daí uses a crisis communication approach that adapts to the situation and conditions of his madú during the COVID-19 pandemic. The contribution of daí in crisis situations becomes an affirmation that Islamic proselytizing is shalih li kulli zaman wa makan or da'wah in harmony with situational and contextual developments according to the space and time that surrounds itOriginality - This study uses crisis communication strategies in amplifying proselytizing messages in the form of akidah, muamalah and akhlak.***Tujuan - Tujuan penelitian ini adalah mengkaji pesan dakwah dan strategi komunikasi krisis yang dilakukan oleh Buya Yahya dalam merespon pandemi COVID-19 di YouTube Al-Bahjah TV pada periode 2020-2022.Metode - Penelitian ini  menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data dengan melalui observasi dan dokumentasi. Teknik analisis data menggunakan analisis isi kualitatif berupa pengkoleksian data, pengkodingan data, analisis data dan interpretasi data.Hasil  -  Hasil penelitian menunjukkan bahwa kontribusi Buya Yahya dalam merespon pandemi COVID-19 di Indonesia melalui YouTube Al-Bahjah TV periode Maret 2020 hingga April 2022 dengan melakukan amplifikasi pesan dakwah sebanyak 76 video.  Hasil dari kategorisasi pesan dakwah Buya Yahya berupa tema syariah mendominasi dengan presentase sebesar 65%.  Tema akhlak dengan presentase sebesar 26%, dan tema akidah sebesar 9%. Komunikasi krisis yang dilakukan Buya Yahya dengan menggunakan strategi pesan berupa instructing information dan adjusting information.Implikasi – Penelitian ini mengeksplorasi kontribusi daí dalam merespon pandemi COVID-19. Daí menggunakan pendekatan komunikasi krisis yang menyesuaikan dengan situasi dan kondisi madú nya pada masa pandemi COVID-19. Kontribusi daí dalam situasi krisis menjadi penegasan bahwa dakwah Islam itu shalih li kulli zaman wa makan atau dakwah selaras dengan perkembangan situasional dan kontekstual sesuai dengan ruang dan waktu yang melingkupinyaOrisinalitas - Penelitian ini menggunakan strategi komunikasi krisis dalam mengamplifikasi pesan dakwah berupa akidah, muamalah dan akhlak